Sexual stage-specific expression of a third calcium-dependent protein kinase from Plasmodium falciparum. - Li, J; Baker, D; Cox, L (2000)
A third calcium-dependent protein kinase (CDPK) gene has been isolated from the human malaria parasite Plasmodium falciparum by vectorette technology. The gene consists of five exons and four introns. The open reading frame resulting from removal of the four introns encodes a protein of 562 amino acid residues with a predicted molecular mass of 65.3 kDa. The encoded protein, termed PfCDPK3, consists of four distinct domains characteristic of a member of the CDPK family and displays the highest homology (46% identity and 69% similarity) to PfCDPK2, the second CDPK of P. falciparum. The N-terminal variable domain is rich in serine/threonine and lysine and contains multiple consensus phosphorylation sites for a range of protein kinases. The catalytic domain possesses all conserved motifs of the protein kinase family except for the highly conserved glutamic acid residue in subdomain VIII, which is replaced by a glutamine residue. The sequence of the junction domain comprising 31 amino acid residues is less conserved. The calmodulin-like regulatory domain contains four EF-hand calcium-binding motifs, each consisting of a loop of 12 amino acid residues which is flanked by two alpha-helices. Southern blotting of genomic DNA digests showed that the Pfcdpk3 gene is present as a single copy per haploid genome. A 2900 nucleotide transcript of this gene is expressed specifically in the sexual erythrocytic stage, indicating that PfCDPK3 is involved in sexual stage-specific events. It is proposed that PfCDPK3 may serve as a link between calcium and gametogenesis of P. falciparum.